Diploid chromosome-scale assembly of the Muscadinia rotundifolia genome supports chromosome fusion and disease resistance gene expansion during Vitis and Muscadinia divergence. Issue 4 (5th February 2021) - Cochetel, Noé; Minio, Andrea; Massonnet, Mélanie; Vondras, Amanda M; Figueroa-Balderas, Rosa; Cantu, Dario
Abstract: Muscadinia rotundifolia, the muscadine grape, has been cultivated for centuries in the southeastern United States. M. rotundifolia is resistant to many of the pathogens that detrimentally affect Vitis vinifera, the grape species commonly used for winemaking. For this reason, M. rotundifolia is a valuable genetic resource for breeding. Single-molecule real-time reads were combined with optical maps to reconstruct the two haplotypes of each of the 20  M. rotundifolia cv. Trayshed chromosomes. The completeness and accuracy of the assembly were confirmed using a high-density linkage map. Protein-coding genes were annotated using an integrated and comprehensive approach. This included using full-length cDNA sequencing (Iso-Seq) to improve gene structure and hypothetical spliced variant predictions. Our data strongly support that Muscadinia chromosomes 7 and 20 are fused in Vitis and pinpoint the location of the fusion in Cabernet Sauvignon and PN40024 chromosome 7. Disease-related gene numbers in Trayshed and Cabernet Sauvignon were similar, but their clustering locations were different. A dramatic expansion of the Toll/Interleukin-1 Receptor-like Nucleotide-Binding Site Leucine-Rich Repeat (TIR-NBS-LRR) class was detected on Trayshed chromosome 12 at the Resistance to Uncinula necator 1 ( RUN1 )/ Resistance to Plasmopara viticola 1 ( RPV1 ) locus, which confers strong dominant resistance to powdery and downy mildews. A genome browser, annotation, and Blast tool for Trayshed are available at www.grapegenomics.com .